The effect of a Mentor Mothers program on prevention of vertical transmission of HIV outcomes in Zambézia Province, Mozambique: a retrospective interrupted time series analysis. Issue 6 (19th June 2022) - Carlucci, James G.; Yu, Zhihong; González, Purificación; Bravo, Magdalena; Amorim, Gustavo; das Felicidades Cugara, Cristina; Guambe, Helga; Mucanhenga, Jaime; Silva, Wilson; Tique, José A.; Sardella Alvim, Maria Fernanda; Graves, Erin; et al.
Abstract: Introduction: Mentor Mothers (MM) provide peer support to pregnant and postpartum women living with HIV (PPWH) and their infants with perinatal HIV exposure (IPE) throughout the cascade of prevention of vertical transmission (PVT) services. MM were implemented in Zambézia Province, Mozambique starting in August 2017. This evaluation aimed to determine the effect of MM on PVT outcomes. Methods: A retrospective interrupted time series analysis was done using routinely collected aggregate data from 85 public health facilities providing HIV services in nine districts of Zambézia. All PPWH (and their IPE) who initiated antiretroviral therapy (ART) from August 2016 through April 2019 were included. Outcomes included the proportion per month per district of: PPWH retained in care 12 months after ART initiation, PPWH with viral suppression and IPE with HIV DNA PCR test positivity by 9 months of age. The effect of MM on outcomes was assessed using logistic regression. Results: The odds of 12‐month retention increased 1.5% per month in the pre‐MM period, compared to a monthly increase of 7.6% with‐MM (35–61% pre‐MM, 56–72% with‐MM; p < 0.001). The odds of being virally suppressed decreased by 0.9% per month in the pre‐MM period, compared to a monthly increase of 3.9% with‐MM (49–85% pre‐MM, 59–80% with‐MM; p < 0.001). The odds of DNA PCR positivity by 9 months of age decreased 8.9% per month in the pre‐MM period, compared to a monthly decrease of 0.4% with‐MM (0–14% pre‐MM, 4–10% with‐MM; p < 0.001). The odds of DNA PCR uptake (the proportion of IPE who received DNA PCR testing) by 9 months of age were significantly higher in the with‐MM period compared to the pre‐MM period (48–100% pre‐MM, 87–100% with‐MM; p < 0.001). Conclusions: MM services were associated with improved retention in PVT services and higher viral suppression rates among PPWH. While there was ongoing but diminishing improvement in DNA PCR positivity rates among IPE following MM implementation, this might be explained by increased uptake of HIV testing among high‐risk IPE who were previously not getting tested. Additional efforts are needed to further optimize PVT outcomes, and MM should be one part of a comprehensive strategy to address this critical need.